Creation, fall, restoration : a biblical theology of creation - Kulikovsky, Andrew S. (Andrew Simeon), 1972- (Fearn, Ross-shire, Scotland : Mentor, 2009)
Andrew S. Kulikovsky brings to the debate among creationists a robust reading of the relevant biblical texts, including the opening chapters of Genesis. He argues that biblical authority applies to the natural world of the sciences and history as well as to matters of faith and conduct. --from publisher description
Why a biblical theology of creation? -- Scripture, science and interpretation -- Creation and Genesis: a historical survey -- The Genesis account: its purpose and function -- Formation, re-creation or creation ex nihilo? -- The days of creation: God's creative activities -- The days of creation: meaning and significance -- Creation of humanity and the Garden of Eden -- The fall and its effects -- The flood and its effects -- Creation, preservation and dominion -- Creation restored.
Includes bibliographical references (p. 286-302) and index.
Keywords: Creation; Creation -- Biblical teaching; Biblical cosmology; Creationism; Creation - Biblical theology of